KECENDERUNGAN SISWA SMA DI BEKASI ~DALAM MEMILIH TOPIK ESAI DITINJAU DARI PERSPEKTIF GENDER - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The relationship between gender and language style has attracted a lot research. This study aims to examine the extent to which high school students in Bekasi, West Java, understand essays and what topics attract them most. The data consist of essays written by 136 students from 3 high schools (3 private high schools and 3 public high schools). In addition, they also include questionaire responses, interviews and direct observation. The results indicate that high school female students in Bekasi, like their male counterparts, choose not only personal topics but also public topics. Both male and female students tend to write essays whose topics are social issues (47%), information technology (14%), personal matters (12%), nationalism (6%) and health (5%). Female students prefer social issues whereas male students prefer information technology. Female students tend to express their feelings openly than male students do. Keywords: gender, essay. writing. topic. discourse